Dynamics of Marriage Dispensation at The Sidenreng Rappang Religious Court After Law No. 16 of 2019: A Comparative Study of Family Law - Masyhud, Luthfiah; Fikri, Fikri; Aris, Aris; Basri, Rusdaya; Sunuwati, Sunuwati (Al-Iftah: Journal of Islamic studies and society, 2025)
This research examines social facts related to marriage dispensation before and after the enactment of Law No. 16/2019 at the Sidenreng Rappang Religious Court. The focus of the research is on the factors causing the increase in marriage dispensation applications and the response of law enforcers in the religious courts. The method used is field research with a qualitative descriptive approach and case study method. The results showed that after the enactment of Law No. 16/2019, which raised the minimum age of marriage to 19 years, there was a significant increase in marriage dispensation applications at the Sidenreng Rappang Religious Court. The main factors influencing the high number of applications include family economic conditions, low levels of education, strong local social and cultural norms, pregnancy outside marriage, and lack of supervision and education from parents. In addition, fear of violating religious norms and a desire to maintain the family's reputation are also important reasons for marriage dispensation applications. Despite various education and socialization efforts by the Sidenreng Rappang Religious Court, the effective implementation of the minimum age of marriage still faces challenges due to deep-rooted social and cultural factors in the community. This study recommends the need for increased legal education, strengthening the role of parents, and synergy between agencies to reduce marriage dispensation.